2016
DOI: 10.1016/j.bbamcr.2016.07.008
|View full text |Cite|
|
Sign up to set email alerts
|

Low dose ouabain stimulates Na K ATPase α1 subunit association with angiotensin II type 1 receptor in renal proximal tubule cells

Abstract: Our laboratory has recently demonstrated that low concentrations of ouabain increase blood pressure in rats associated with stimulation of Na-K ATPase activity and activation of the Src signaling cascade in NHE1-dependent manner. Proteomic analysis of human kidney proximal tubule cells (HKC11) suggested that the Angiotensin II type 1 receptor (AT1R) as an ouabain-associating protein. We hypothesize that ouabain-induced stimulation of Na-K ATPase activity is mediated through AT1R. To test this hypothesis, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…These effects were prevented by the angiotensin II type 1 receptor (AT1R) blocker candesartan. The authors concluded that in renal proximal tubule cells, ouabain stimulates Na + ,K + -ATPase through an angiotensin/AT1R/Src/ERK1/2-dependent mechanism [ 93 ]. This signaling pathway is considered in more detail below.…”
Section: Evidence For Na + I K mentioning
confidence: 99%
“…These effects were prevented by the angiotensin II type 1 receptor (AT1R) blocker candesartan. The authors concluded that in renal proximal tubule cells, ouabain stimulates Na + ,K + -ATPase through an angiotensin/AT1R/Src/ERK1/2-dependent mechanism [ 93 ]. This signaling pathway is considered in more detail below.…”
Section: Evidence For Na + I K mentioning
confidence: 99%
“…The therapeutic window is narrow, however, and CTS have also been used as potent neurotoxins. CTS have been shown to stimulate signaling cascades through NKA at much lower concentrations than needed to impact ion transport 712 . These signaling functions are mediated by localized intracellular activation of Src-family kinases (SFK) and are independent of ion transport; because of the differences in dose response it is possible to activate NKA-mediated SFK signaling without altering Na/K homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Low doses of Ouabain also reduce inflammatory cytokine production in LPS treated rats by blocking the nuclear translocation of NF-kB [ 20 ]. At low picomolar concentrations Ouabain promotes an interaction between the pump and the Angiotensin Type 1 Receptor (AT1R) [ 21 ]. It has also been demonstrated that AT1R directly interacts with ACE2 [ 22 ], the port of entry for the SARS and SARS-2 [ 23 ] coronaviruses.…”
Section: Resultsmentioning
confidence: 99%